Đặc điểm thành phần, chất lượng sét gốm khu vực Nho Quan tỉnh Ninh Bình - Huyên, Nguyễn Xuân (Vietnam Journal of Earth Sciences, 2012)
summary Composition and quality of ceramic clays of Nho Quan, Ninh Binh Pottery clays of the Ninh Binh province are mainly distributed in the Nho Quan. Two types of pottery clay origins have been discovered, weathering clay in Song Boi Formation (T2-3 sb) and sedimentary clay associated with the Vinh Phuc Formation (Q13vp). Weathering pottery clays are less promising, since their limited distribution on the slopes and coastal hills and uneven quality; the sedimentary origin clay have wide distribution area and great potential, with stable thickness, elongated from a few hundred meters to several kilometers. The results of grain size analysis, mineral composition and chemical composition (SiO2, Al2O3, Fe2O3, TiO2, CaO, MgO, Na2O, K2O, SO2 ...) and other technical characteristics (stretching and plastic limits, water absorption, porosity, high refractory, heating, shrinkage, ...) of the pottery clay shows that they meet the requirement for ceramic production, according to the Vietnam standard No 6300-1997. Mixing tests of the clays at the study area with those from neighborhood area, the trial production of tiles, decorative ceramic bricks, red tiles, as well as fine art pottery imply the very good quality, equivalent to similar products are sold on the market today